2016
DOI: 10.3311/ppch.8482
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of CaCl 2 Incorporated Polyethersulfone Ultrafiltration Membranes

Abstract: Poly(ethersulfone) (PES) / poly(vinylpyrrolidone) (PVP) blend

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The obtained results as shown in Table , clearly indicate that the surface roughness of the fabricated membrane increase with increase in SCER content. It has been reported that membranes with lower surface roughness have stronger antifouling abilities . The fouling capability tends to increase with increase in surface roughness due to accumulation of solute in the node of the rough membrane surface .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results as shown in Table , clearly indicate that the surface roughness of the fabricated membrane increase with increase in SCER content. It has been reported that membranes with lower surface roughness have stronger antifouling abilities . The fouling capability tends to increase with increase in surface roughness due to accumulation of solute in the node of the rough membrane surface .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that membranes with lower surface roughness have stronger antifouling abilities. [45][46][47] The fouling capability tends to increase with increase in surface roughness due to accumulation of solute in the node of the rough membrane surface. 46 Hence the fabricated membrane with low value of SCER were expected to have better antifouling resistances.…”
Section: Pore Size Analysismentioning
confidence: 99%
“…Membrane technology has vast applications in various industrial processes, namely in waste treatment [1,2], food and biotechnology industries [3], metal industries [4], textile industries [5][6][7], chemical process industries [8], water production [9] and bacteria/virus removal applications [10]. In general, membranes can be classified based on their morphologies including dense homogenous polymer membranes, porous membranes and thin-film composite membranes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic fractions of foulants deposit on the membrane surface and cause irreversible fouling, while the hydrophilic fractions are less likely to accumulate on the membrane surface. Therefore, various techniques have been developed to prevent fouling by enhancing the hydrophilicity of membranes such as coating, blending, plasma treatment, and surface grafting . Blending with hydrophilic polymers, such as PEG and PVP, is one of the most popular approaches, but water‐soluble polymers leach out of the membrane matrix and a small portion of hydrophilic additive remains in the membrane matrix and on the surface …”
Section: Introductionmentioning
confidence: 99%